Ten-year longitudinal study on the state of dentition and subjective masticatory ability in community-dwelling elderly people. Issue 3 (July 2016) - Sato, Naoko; Ono, Takahiro; Kon, Haruka; Sakurai, Naoki; Kohno, Shoji; Yoshihara, Akihiro; Miyazaki, Hideo
Abstract: Purpose: The aim of this study was to reveal whether the differences in further loss of teeth and occlusal supports, and change in masticatory ability depend on the status of dentition at the age of 70 in community-dwelling elderly people. Methods: A 10-year longitudinal survey was carried out on 349 (176 females and 173 males) elderly subjects. The subjects to be analyzed were classified into four groups in accordance with the classifications of Miyachi's Triangular Classification. Zone A: subjects with ten or more occlusal supports. Zone B: those with nine to five occlusal supports. Zone D: those with four or fewer occlusal supports and 11 or more remaining teeth. Zone C: those with ten or fewer remaining teeth. The numbers of remaining teeth and occlusal supports were recorded in both examinations. Questionnaires regarding their food intake status were given to subjects. Results: Subjects in Zone B had greater numbers of teeth loss than those in Zones A and C. Subjects in Zone B and D lost greater numbers of occlusal supports than subjects in Zones A and C. The number of food items that could be chewed had significantly decreased in subjects who remained in Zone A and those who changed from Zone B to Zones D and C. Conclusions: It was shown that various states of dentition classified by Miyachi's Triangular Classification at the age of 70 resulted in different numbers of remaining teeth and occlusal supports and changes in masticatory ability 10 years later in community-dwelling elderly people.